Canal transportation and centering ability of curved root canals prepared using rotary and reciprocating systems - Marlos Barbosa Ribeiro; Silvio José Albergaria; Maria de Fátima Gesteira Malvar; Iêda Margarida Crusoé-Rebello; Brenda Paula Figueiredo de Almeida Gomes; Fabíola Bastos de Carvalho (Universidade Estadual de Campinas, 2015)
resumo